Public Forgetting : The Rhetoric and Politics of Beginning Again - Vivian, Bradford (Book collections on Project MUSE., 2010)
"Reconsiders the negative status attributed to forgetting in both academic and popular discussions of public memory. Demonstrates how a community may adopt idioms of forgetting in order to create new and beneficial standards of public judgment concerning the lessons and responsibilities of its shared past"--Provided by publisher